Response Water Spinach (Ipomoea Aquatica) to Different Medium Treatment with AB Mix Nutrients on The Cultivation Hydroponic DFT (Deep Flow Technique) - Nur Khozin, Mohammad; Sandy Al Firdauzi; Nada Nur Rizkiyah; Raihan Hidayatullah; Sigit Soeparjono (Journal of Soilscape and Agriculture, 2023)
Water spinach (Ipomoea aquatica) is a plant that is included in the type of vegetables and is widely cultivated as food. Every year the demand for water spinach in the market continues to increase, besides that consumers also want the quality of water spinach which is more nutritious, clean, and hygienic. Therefore, hydroponic water spinach is used to support consumer demand in the market. In addition, by cultivating water spinach hydroponically as well as an alternative to farming in narrow areas. In hydroponic cultivating water spinach, there are several things that need to be considered, such as the provision of nutrition, the planting media used, and what hydroponic system will be used. This study aims to determine the response of water spinach plants to the treatment of different planting media, as well as to obtain information about what planting media is suitable for use in the DFT water spinach hydroponic system to support its growth and development. The experimental method used was a completely randomized design, which consisted of three different levels of treatment, namely the use of rockwool, charcoal, and moss media. The results of this study of differences in planting media showed the treatment with the best tendency for the parameters of plant height, number of leaves, and plant fresh weight